ANALYSIS OF STUDENT NEEDS FOR INTEGRATING SUKHINAH FAMILY MATERIAL IN HINDU HIGHER EDUCATION - I Putu Suyasa Ariputra; Encep Syarief Nurdin; Yadi Ruyadi; Kadek Aria Prima Dewi PF; Mupid Hidayat; Warlim; Asep Dahliyana (UHN I Gusti Bagus Sugriwa Denpasar, 2026)
This study was motivated by the urgency of strengthening moral and spiritual values grounded in Hindu teachings to build family resilience and student character rooted in dharma. This urgency is increasingly apparent with the high divorce rate among young Hindu families and the phenomenon of sing beling sing ngantén, which is increasingly emerging among Balinese society. This study aims to identify the need to integrate sukhinah family material into the Compulsory Subjects of the Hindu Religious Education Curriculum at Hindu Universities. The research method used a quantitative approach involving 200 student respondents from the Dharma Duta Faculty, UHN I Gusti Bagus Sugriwa Denpasar. The data were analyzed using descriptive statistics and multiple linear regression to test the influence of knowledge, learning experience, and perception of relevance on the need for material integration. The results showed that all three variables had a significant simultaneous effect on the need to integrate sukhinah family material into the compulsory Hindu Religious Education curriculum. Perception of value relevance was the most dominant variable, followed by learning experience, while theoretical knowledge had a significant adverse effect. These findings emphasize the importance of integrating sukhinah family material into compulsory courses in the Hindu Religious Education curriculum, using an experiential learning approach, and of internalizing sukhinah family values in a contextual and applicable manner to strengthen the character and resilience of Hindu students’ families.